Answer:
h(x) = 2^(x) - 1.
Step-by-step explanation:
Let's look at each equation:
f(x) = -3x +7, Well as x increases, since it's multiplication, there are "going to be more" -3's, so it's going to be decreasing.
g(x) = -4(2^x). While 2^x is increasing, because "there are going to be more 2's multiplied by each other" as x increases, it's being multiplied by a negative number, so it's actually going to be decrasing
h(x) = 2^(x) - 1. Here's it's going to be increases as x goes towards infinity because "there are going to be more 2's multiplied by each other", and there isn't any negative sign, while there is a negative 1, it's constant, so the overall value will be increasing
Answer:
m<A = 84
AC = 9
Step-by-step explanation:
We can find the measure of Angle A by using the sum of interior angles of a triangle theorem.
48+48+A=180
96+A=180
A=84
We can then use the isosceles triangle similarity theorem and reason that since this is an isosceles triangle and one of the side lengths (AB) is 9, the other (AC) would also be 9.